HUBUNGAN TINGKAT STRES DAN KECEMASAN DENGAN KUALITAS HIDUP PADA LANSIA DI RW.04 DAN RW.05 KELURAHAN BOJONG GEDE KABUPATEN BOGOR - Nada Saskia, (2020)
In the elderly there is an aging process in which there is a decline in bodily functions that can interfere with daily activities so that elderly experienced a sense of hellessness that will cause stress and anxiety to reduce the quality of life in the elderly. This research aims to determine the relationship of stress and anxiety levels with quality of life in elderly in RW. 04 and RW. 05 Bojong Gede Village, Bogor Regency. Researchers used this type of quantitative correlation research with cross sectional research designs to connect variables in this study. Purposive sampling techniques were used in this study, as many as 40 elderly respondents. The results showed a p value of 0.020 (p <0.05) along with an OR value of 0.144 on the bivariate variable stress level with quality of life and a p value of 0.009 (p <0.05) along with an OR value of 0.118 on the bivariate variable anxiety with quality of life which means that there is a relationship between stress and anxiety levels with quality of life in the elderly. Social support from family, close friends, neighbors and infrastructure in the form of adequate health services can help the elderly in improving their quality of life.